Evaluation of a test module to measure relevant components of ball release height in jump throws in team handball - Jäger, J. M.; Gail, S.; Müller, H. (Journal of Human Sport & Exercise, 2017)
This study aims to analyse different performance factors of jump throws in team handball. These factors cover anthropometric prerequisites (body height and Standing Reach Height - SRH), general jump abilities (Jumping Reach Height during a countermovement jump - JRH), aspects of the jump technique (Ball Height during a handball specific Jump - BHJ) as well as the throwing technique (Ball release Height during a jump Throw - BHT). 36 male team handball players from three different senior leagues were analysed to quantify the extent to which these components vary with competitive levels and playing positions. Additionally, 30 subjects (highest national junior league) were recruited to examine the appropriateness of the components with respect to predicting ball release heights in jump throws. Results show that SRH, JRH, BHJ and BHT differ significantly between leagues and playing positions. Furthermore, the prediction of BHT based on body height, SRH, JRH, and BHJ explained approx. 62 % of the variance in BHT compared to 15 % explained by the traditionally used jump and reach test (JRT). Thus, the factors measured in the test module seem to capture relevant information regarding the level of expertise and may be strong predictors of ball release height in jump throws. Results are discussed with respect to consequences for training and coaching in team handball.